Study on the Driving Effect and Mechanism of Industrial Water Use in Guangzhou City - CHEN Yi; YU Haixia; LIU Bingjun (Renmin Zhujiang)
In order to explore the change law and driving factors of industrial water use in Guangzhou,this paper divides the influencing factors of industrial water use into economic development level,population size,water use efficiency and industrial structure by the Kaya identity and Logarithmic Mean Divisia Index (LMDI),and analyzes the effects of various factors on the changes in industrial water use in Guangzhou from 2000 to 2015.The results show that:The economic development effect and population size effect are the primary and secondary driving factors for the increase on the industrial water use in Guangzhou,with cumulative contribution values of 8.538 billion m3 and 4.583 billion m3,respectively;The water use efficiency effect and industrial structure effect are the primary and secondary inhibiting factors for the increase on the industrial water use in Guangzhou,with cumulative contribution values of -11.789 billion m3 and -2.547 billion m3,respectively.